Alignment of inter-firm performance measures in contractual alliances as a predictor of relationship success - Rey-Marston, Maria (Cranfield University, 2013)
This research explains the role of aligned inter-firm performance measures as a predictor of success in of contractual alliances. Contractual alliances, a popular type of inter-firm relations, are also known as non-equity alliances and often display conflicting objectives in their contractual agreements. This research proposes that the assessment of contractual alliances performance must go beyond the contract’s ability to deliver to its internal performance targets or service level agreements (SLA). The success of contractual alliances lies in the alliance’s capability to contribute to the specific performance objectives of the firms involved as well as to fulfil its internal SLAs. This capability is called alignment and the results of this research show that is critical to the success of inter-firm relationships. The data for the research was gathered from outsourcing contracts between a logistics service provider and 149 users. Each contract includes its SLAs and two years of actual performance measures. The research design considers the firms’ financial measures as a proxy for their performance objectives during the same period of time. The alignment construct was operationalised by creating an inter-firm alignment (IFA) coefficient calculated with mathematical techniques to assess multi-dimensional fit amongst constructs. The three dimensions included in the IFA coefficient are i) alignment of contract’s SLAs and actual performance values, ii) alignment of contract’s SLAs and provider’s performance objectives, and iii) alignment of contract’s SLAs and user’s performance objectives. Success of contractual alliances was operationalised using known measures from the inter-firm management literature, such as longevity, stability, formality and relative profitability of the relationship. Information for all determinants was available in the 149 contracts. The quantitative correlations were specified and calculated using structural equation models (SEM). The results show that aligned inter-firm performance measures are a strong predictor of contractual alliance success. The empirical model supports the positive correlation of longevity and formality as measures of contractual alliance success, as stated in extant literature. The findings dispute the expected positive correlation between formality and stability with alliance success as described in the alliance literature. The results confirm the positive role of renegotiations as stated in the organization learning literature. Additional in-depth interviews were conducted with relationship managers, during the pilot study. The qualitative results support the quantitative findings. This research contributes to theory by: a) conceptualising and measuring the concept alignment to inter-firm performance measures; b) estimating the contribution of relation-specific measures to contractual alliance success, and c) introducing alignment of inter-firm performance measures as a predictor of contractual alliance success. The research and its results fill a substantive gap in managing contractual alliances. It provides the outsourcing industry with a tool that predicts the likelihood of relationship survival based on the degree of alignment of the inter-firm’s performance measures. The quantitative methods employed in the research extend the use of current techniques for assessing ‘fit’ in the strategy literature, into the field of performance measurement systems.
Keywords: co-alignment; strategic fit of performance measures; inter-firm relationships; alliance success; longevity; renegotiations; successful logistics outsourcing; aligned metrics; performance measurement systems